Color Analysis on Indonesia Top e-Commerce - Pinandita, Arsita; Nofrizaldi, Nofrizaldi; Muhammad, Arif Wirawan (Budapest International Research and Critics University, 2021)
The e-commerce usage is a must in the business industry; think more complex problems that require to always keeping up with the global developments which requires to taking a creative action. Statista reported (data.tempo.co) regarding data on the top 10 most visited Indonesia e-commerce sites, Shopee ranks first with 71.53 million clicks per month in the first quarter of 2020. Tokopedia is in the second place with 69 million clicks per month during the first quarter of 2020. The color identity usage in e-commerce has a strong perception in the brand image forming. In e-commerce, the color psychology usage is the one of supports to attract attention, selling products early, raise offer, build messages and product images, and showing identity. Color is universal languages that cross the cultural boundaries in technology which is currently called the global village. This study aims to provide an understanding of the color benefits in the brand identity form which is applied through e-commerce displays.